Nutritional and medicinal value of some important arid zone fruits of Rajasthan (Indian Journal of Arid Horticulture, 2020)
Arid fruits are the special gifts of nature to the human being grown in the arid climatic conditions. Arid fruits have very good nutritional values and survive in very adverse climatic condition. Protein, fat, fibers, vitamins, mineral etc. are found in greater amount in arid fruits as compared to tropical and sub-tropical fruits. Still very less studies has been conducted on arid fruit especially nutritional aspects. Various fruit plants found in Rajasthan having high medicinal properties. Underutilized fruits provide food, nutrition and health promoting substances to native communities and are an additional source of income. To achieve nutrition and income security for the people, particularly in arid region, suitable species are of vital importance. Arid fruits viz. aonla (Emblica officinalis), bael (Aegle marmelos), jamun (Syzygium cumini), pomegranate (Punica granatum), custard apple (Annona squamosa), karonda (Carrisa carandus), phalsa (Grewia subinequalis), lahsua/lasora (Cordia myxa), etc. possess high nutritional values. Hence, research and development work, farmers awareness and feasibility for cultivation of these less known fruits are to be given due consideration. The objective of this review article is to concisely summarize the information about the important and underutilized arid fruits of Rajasthan with reference to their nutritional values and medicinal uses.
Keywords: Arid zone fruits; medicinal properties; nutritional value; underutilized fruits